Anodic stripping voltammetry at hydrodynamic mercury thin film electrodes. Part 2. Numerical simulation of stripping peaks for irreversible and quasireversible processes - Ball, J; Compton, R (1997)
The time dependent backwards implicit method is used to simulate the shape and position of the stripping peaks in DC (linear scan) anodic stripping voltammetry at mercury thin film hydrodynamic electrodes for electrochemically irreversible and quasireversible systems assuming that the electrode diffusion layer thickness is uniform, as in the case of a rotating disk electrode. The effect of the electrochemical rate constant in influencing both the peak potential and peak shape is examined and the conditions identified under whch electrochemically reversible behavior is approached.